Learning Styles, self-concept, and academic performance in health Professional Training - Márquez Hernández, Enrique; Caballero García, Presentación Ángeles (Journal of Learning Styles, 2024)
Attention to diversity is central to current educational reform. It is crucial for teachers to determine which methods or variables improve learning. On this basis, we studied the relationship between learning styles, self-concept and academic performance. The methodology was non-experimental, cross-sectional, correlational and predictive. The sample consisted of 67 non-randomly and purposively selected Spanish students of Vocational Health Training. We assessed learning styles with the CHAEA-36 (Maureira, 2015), self-concept with the AF-5 (García & Musitu, 1999), and performance, with the school's report cards. The results indicate a moderate preference for reflective and theoretical learning styles, and a low preference for active and pragmatic learning styles. Family self-concept predominates, followed by academic, social, physical and emotional self-concept. Average academic performance is remarkable. Academic and physical self-concept correlates positively and poorly with performance, and pragmatic self-concept negatively and poorly. Finally, pragmatic style and academic self-concept predict performance (by 7.1% and 9.8%, respectively, in isolation, and by 10.6% jointly). The data are discussed for their educational implications.
Keywords: Learning styles; self-concept; academic performance; professional training; attention to diversity